Given: 3x2 - x - 2 = 0
9x2 - 3x - 6 = 0 (multiplying both sides by 3)
9x2 - 3x = 6
(adding on both sides)
using a2 - 2ab + b2 = (a - b)2
(taking square root on both sides)
Hence the roots of equation are
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation